Better nitrogen fertilizer management improved Mchare banana productivity and profitability in northern highlands, Tanzania - Meya, A.I.; Swennen, R.; Ndakidemi, P.A.; Mtei, K.M.; Merckx, Roel (MDPI, 2023)
Declining land productivity is a major problem constraining banana (Musa spp.) production in Tanzania. Banana fruit yield consequently reaches only 15% of the potential, primarily due to inadequate soil nutrient replenishment. Improving farmers’ soil nutrient replenishment strategy in banana home gardens, which relies on applications of cattle manure only, by mixing with inorganic fertilizer resources can increase land productivity and can improve the overall profitability of banana production in the country. Experiments were conducted at Tarakea, Lyamungo, and Tengeru to determine the effects of organic fertilizer resources (animal manure and crop residue) and their combination with inorganic fertilizer resources on the productivity and profitability of Mchare banana production. Banana fruit yield differed significantly among the experimental sites, with drier areas of Tengeru recording, on average, 19.6 t ha−1 year−1, while the more humid areas of Lyamungo recorded, on average, 39.3 ha−1 year−1. Mchare banana plants grown under sole inorganic fertilizer produced significantly low yields (33.0 t ha−1 year−1) compared with those fertilized with cattle manure only, which lifted the yields to 38.8 t ha−1 year−1, but the latter required more labor input. Soil nitrogen (N) fertilization via cattle manure + mineral fertilizer gave the highest average banana fruit yield (43.0 t ha−1 year−1) across the sites, and reduced fertilization costs by 32%. Subsequently, this integrated fertilization technique generated the highest average net benefits in all sites and both cropping cycles. Thus, the findings of this study form a basis to improve land productivity and profitability in banana-based home gardens in the study area by directing more labor input to good soil N management.